2017
DOI: 10.1088/1674-1056/26/5/058102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-type semiconductor diamonds with sulfur, boron co-doping in FeNiMnCo-C system at high pressure and high temperature

Abstract: A series of diamonds with boron and sulfur co-doping were synthesized in the FeNiMnCo-C system by temperature gradient growth (TGG) under high pressure and high temperature (HPHT). Because of differences in additives, the resulting diamond crystals were colorless, blue-black, or yellow. Their morphologies were slab, tower, or minaret-like. Analysis of the x-ray photoelectron spectra (XPS) of these diamonds shows the presence of B, S, and N in samples from which N was not eliminated. But only the B dopant was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…11 Recently, the study of co-doped diamonds has attracted wide attention, and these results show that synergistic doping can significantly improve the electrical transport performance of diamonds. 12–14 The resistivity of B–H co-doped diamond reached 3.34 × 10 2 Ω cm. However, almost all these studies use two types of reagents as additives.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, the study of co-doped diamonds has attracted wide attention, and these results show that synergistic doping can significantly improve the electrical transport performance of diamonds. 12–14 The resistivity of B–H co-doped diamond reached 3.34 × 10 2 Ω cm. However, almost all these studies use two types of reagents as additives.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] At present, the main synthetic method of diamond growth is the high pressure and high temperature (HPHT) static pressure method using metal catalyst as medium. [9][10][11] Generally, graphite dissolves in the melt of alloy catalysts, whose components are Fe, Ni, Co, Mn, Cr, etc., and precipitates to grow as diamond under HPHT. It is difficult to avoid trapping some metallic impurities in crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported that type-Ib or IIa with single-S doping and BS co-doping high-quality large diamonds with n-or p-type semiconductor properties were synthesized. [20,21] It is pointed out that there is no change in the color of type-Ib with S or BS co-doping. In contrast, the color of type-IIa diamond changes from colorless to blue and black with the increase of additive B content.…”
Section: Introductionmentioning
confidence: 99%